2011
DOI: 10.1371/journal.pone.0027098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of HIV-1 CRF01_AE Env in Thai Patients

Abstract: BackgroundThe envelope glycoproteins (Env), gp120 and gp41, are the most variable proteins of human immunodeficiency virus type 1 (HIV-1), and are the major targets of humoral immune responses against HIV-1. A circulating recombinant form of HIV-1, CRF01_AE, is prevalent throughout Southeast Asia; however, only limited information regarding the immunological characteristics of CRF01_AE Env is currently available. In this study, we attempted to examine the evolutionary pattern of CRF01_AE Env under the selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…Furthermore, CRF01_AE variation at H375 is minimal, even though the C3 region showed the highest rates of amino acid diversity among conserved regions of gp120 and appeared important in CRF01_AE HIV-1 quasispecies evolution (6). Coupled with the finding that all other subtypes and CRFs analyzed have greater entropy and an absolute nonoccurrence of H at gp120 position 375, our observations suggest that H375 may confer an evolutionary advantage/constraint in the context of CRF01_AE HIV-1 infection, distinct from the drug resistance observed in this study.…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, CRF01_AE variation at H375 is minimal, even though the C3 region showed the highest rates of amino acid diversity among conserved regions of gp120 and appeared important in CRF01_AE HIV-1 quasispecies evolution (6). Coupled with the finding that all other subtypes and CRFs analyzed have greater entropy and an absolute nonoccurrence of H at gp120 position 375, our observations suggest that H375 may confer an evolutionary advantage/constraint in the context of CRF01_AE HIV-1 infection, distinct from the drug resistance observed in this study.…”
Section: Figmentioning
confidence: 96%
“…Since CD4-F43 insertion into the CD4-F43 cavity (Fig. 6H, I) accounts for 23% of the CD4-gp120 interaction face (6,32) and is critical for HIV-1 entry into host cells, this competition (Fig. 6F, G, K) could account for the strong subtype B HIV-1 inhibition demonstrated by this drug.…”
Section: Evaluation Of Entry Inhibitors Against Hiv-1mentioning
confidence: 99%
“…In addition, structural differences between subtype B and C Env molecules have recently been reported [31]. Moreover, our recent observations suggested that different Env regions were affected by host immune pressure between CRF01_AE and subtype B viruses [32]. Taken together with the results in this report, we believe that it is important to take into account the antigenic and immunogenic diversity among different subtypes and CRFs of HIV-1 in developing HIV-1 vaccine antigens to elicit a broadly neutralizing antibody response.…”
Section: Discussionmentioning
confidence: 77%
“…Our previous report showed that high amino acid variability was observed in the V2 region, as well as in the V1, V4 and V5 regions, of Env gp120 among viral genomic fragments continuously collected for a short period (3 years) from CRF01_AE-infected Thai individuals [ 48 ], suggesting that the virus constantly evolved by introducing mutations in the V2 region of gp120, presumably in order to counteract anti-HIV-1 humoral immune responses. Env gp120 and gp41 are the major targets of anti-HIV-1 neutralizing antibodies, and are therefore candidates for vaccine antigens.…”
Section: Discussionmentioning
confidence: 99%